La metodología, aprendizaje basado en problemas para optimizar el proceso enseñanza-aprendizaje de la asignatura de biología, en el segundo curso de bachillerato general unificado, del colegio “Manuel Ignacio Monteros Valdivieso” año lectivo 2018 - 2019, del cantón Loja - Quiñónez Cuenca, Jhandry Patricio (2020)
The present research is projected as a methodology to support the teaching-learning process in the subject of Biology, as a general objective it was projected: the implementation of the methodological strategy of teaching Learning Based on Problems (ABP), in order to optimize the teaching-learning process in the second year high school students corresponding to the Biology subject; the intervention proposal was built, the same one that was applied in the classroom work during the 2018-2019 academic period; using contents of unit three corresponding to Genetic, applying it as an innovative methodology to improve the academic results of the students. The evaluation of the effectiveness of the proposal was carried out by applying suitable instruments such as the survey that allowed the validation of the work methodology in the subject of Biology; The results made it possible to carry out the analysis and contrast corresponding to the research carried out. The results obtained were that 18 students, 16 of which correspond to 88.89%, indicated that the proposal under investigation has an active, critical and reflexive participation by the students; Likewise, 16 respondents corresponding to 88.89% indicated that it is a different method than the one used by the Teacher and at the same time motivating because it stimulates the discussion and dialogue around a topic in the student. The present research work as an innovative methodology based on constructivism, is directed that from a problem proposed by the teacher, knowledge can be reached through the cognitive conflict of the student.